HEALTH RISKS OF SULFUR DIOXIDE (S02) TAXATION IN COMMUNITIES IN RESIDENTIAL SURROUNDING INDUSTRY PT. DIAN SWASTATIKA SENTOSA POWER IN KONAWE SELATAN DISTRICT: RISKS OF SULFUR DIOXIDE TAXATION - Ikhsan Dwianto; Sunarsih Sunarsih; Erwin Azizi Jayadipraja (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2021)
Background:Sulfur dioxide (S02)and fine particles are one of the emissions produced by coal-fired power plants which are harmful to breathing because they can damage the airways, causing irritation of the walls of the tubes and blocking the smooth passages in the lungs. Methods:This research is an observational study with the study method of Environmental Health Risk Analysis. The location of this research is in the area of the PT. DSSP in Konawe Selatan District. The population is 2,723 people and the human sample is 337 respondents usingClustersampling. While environmental samples (air) were divided into 4 locations where air concentration measurements were carried out in the morning, afternoon and evening. Results:The average sulfur dioxide intake of respondents at point 1 has a mean of 0.0101, at point 2 has a mean of 0.0084, at point 3 has a mean of 0.0105, and at point 4 has an average of 0.0101. Meanwhile, the respondent's risk level for sulfur dioxide RQ> 1 was 5 people. Conclusion:Risk is influenced by body weight, rate of inhalation, time of exposure, frequency of exposure, duration of exposure. Risk management is carried out by reducing exposure time, planting trees that can absorb air pollution, maintaining endurance, implementing safe residential locations from the center of the factory which should be above 2.5 km.